Polymorphisms in the 5′-UTR of PTEN and other gene polymorphisms in normal Japanese individuals - Ohsaka, Y.; Nishino, H. (Цитология и генетика, 2012)
Polymorphisms are distributed differently in populations, including those of regions, ethnic groups, and diseased patients. In order to investigate variation in nucleotide sequences in normal individuals, we isolated genomic DNA from the blood of healthy Japanese individuals and sequenced the 5'-untranslated region (5'- UTR) of the phosphatase and tensin homolog deleted on chromosome 10 (PTEN) gene and the gene promoter, intron, and exon nucleotides of p53, p14ARF, murine double minute 2 (MDM2), and the β2- and β3-adrenoceptor (-AR). We found polymorphisms in these regions, including a deletion at positions –465 to –463 and a substitution at position –404 in PTEN and a substitution at position –4924 in p14ARF, in normal individuals. Individuals with or without the PTEN polymorphism harbored a different distribution of polymorphisms, including simultaneous alterations in nucleotides of p53, MDM2, and β3-AR, and also harbored some polymorphic nucleotides located in the same set of associatively altered nucleotides. Our results show that multiple nucleotides, including the PTEN nucleotides, are altered in normal Japanese individuals and provide useful information for genotyping studies in individuals and populations.